Phytopharmacotherapeutic and Antimicrobial Attributes of Bitter Apple (Citrullus colocynthis) - A Review - T. T., Banjo; Y. O., Aina; F. A., Falade (Covenant Journal of Physical and Life Sciences, 2021)
Emergence of drug-resistant microorganisms over the past few decades has resulted in the search for bioactive compounds potent against these microorganisms. Phytochemicals derived from plants have shown positive curative properties and can be extracted from any part of the plant such as the roots, stem or flower. Bitter apple (Citrullus colocynthis) has been used traditionally for the treatment of infectious diseases and this has stimulated pharmacological interest in the active ingredients responsible for its medicinal properties. The plant also possesses several biological and pharmacological activities including anti-inflammatory, antidiabetic, antimicrobial, anticancer, and antioxidant. This review discussed the phytochemicals present in C. colocynthis, their mode of action and their antimicrobial attributes.